Notas sobre Iberis II. - Moreno, Margarita; Portela, Isabel (Botanica Complutensis, 1989)
. The Ji nazarila Moreno area is amplified because of its presence in Albacete province. The attached of atipie specimens to 1. contracta Pers. are cbecked. The attached of 1. PA ULARENSIS Pau to Ji CONTRA CTA Pers. is discussed.